Toxic ka kasi! exploring the context of toxicity among junior high school students and it influence on their emotional well-being - Martin, Calista Renee Espada; Mentay, Maxinne Marie R.
This study aims to explore junior high school students' perceptions of toxicity in the school environment and its influence on their emotional well-being. A sequential exploratory method was used, consisting of two phases: a custom-designed survey in Phase One, followed by semi-structured Focus Group Discussios (FGDs) in Phase Two. The survey gathered 157 responses, which were analyzed using content analysis. In Phase Two, 28 students participated in four FGDs, analyzed thorugh thematic analysis. The findings revealed that students recognize toxicity through varied experiences such as peer conflicts, student attitudes, and negative academic dynamics, with emotional responses ranging from distress and withdrawal to optimism and resilience. Coping strategies were both adaptive, such as seeking faith, self-reflection, and social support, and maladaptive, including avoidance and isolation. Thus, the researchers have concluded: a) JHS students understand "toxic" as context-dependent behaviors that harm relationships and self-concept, b.) behaviors such as peer conflicts, negative attitudes, and academic distress were associated with school-based toxicity, c.) toxicity in school influenced the students' emotional well-being ranging from distress to resilience as their reaction varied from developmental stage, cultural values, and coping mechanisms. Thus, these underscore the need for comprehensive, supportive, and context-sensitive intervention in schools.